Researching conflict-related sexual violence: a conversation between early-career researchers - Schulz, Philipp; Kreft, Anne-Kathrin (International feminist journal of politics, 2021)
March 2019. It was a brisk spring day in Toronto. We were having lunch in the crowded food court opposite the conference hotel. This was the first time that we had sat down and openly spoken about the toll that researching conflict-related sexual violence (CRSV) in the context of our PhD education has taken on our mental well-being. We both felt grateful for having had the opportunity to have this conversation with each other, as our exchange had helped both of us to better understand and situate the difficulties with which we had been grappling in the preceding months. With this piece, we want to extend that conversation, and hope to increase transparency about research processes and researchers’ mental well-being and to encourage more open, honest, and vulnerable exchanges between researchers working on sensitive issues. Strong emotional reactions to research are, of course, not unique to the study of CRSV. Informal conversations with other (junior) colleagues researching a range of difficult issues – such as armed conflict, terrorism, torture, and genocide – suggest that negative effects on researcher well-being are quite common. These informal exchanges also reveal a persistent lack of information, resources, and institutional support – especially in PhD programs and for first-time field researchers – and a shortage of platforms for frank, honest, and vulnerable discussion about the emotional (and other) challenges involved in doing this kind of work. While we draw here on our experiences researching CRSV – against women in Colombia (Kreft 2019a, 2020) and against men in northern Uganda (Schulz 2018) – we hope that our reflections will also be relatable for (junior) scholars in adjacent research fields. What our conversation shows is that even though we carried out fieldwork in different contexts, under somewhat different conditions, and with different foci, we encountered many of the same challenges and had fairly similar affective responses to our research. While we refrain from making sweeping claims about the representativeness of what we encountered, it becomes apparent that ours are more than isolated experiences. We also fully acknowledge that long-term fieldworkers or practitioners encounter challenges beyond what we discuss here, including not being able to easily “step away” from their work and return home, as we were able to. These challenges should form part of a larger conversation on difficult and sensitive research, but are beyond what we can address in this piece based on our own subjective experiences and our respective positionalities as early-career researchers. By discussing our own experiences, it is also absolutely not our intention to de-center the impact that this type of research has on research participants. Instead, we seek to put the latter in relation to our reflections where applicable, without presuming to truly understand the unique challenges confronting victim-survivors. Finally, we hope that this piece will reassure those encountering difficulties similar to ours, but possibly lacking a conversation partner, that their experiences are not uncommon.